Symposium 1: Learning Technologists: Split Personality or Community of Practice? Symposium Introduction - Armitage, Susan (Proceedings of the International Conference on Networked Learning, 2004)
As the use of Virtual Learning Environments in support of learning and teaching extends across an increasing proportion of HE practice, issues arise for learning technology practitioners related to the move from small to large scale support for such activity. Addressing these issues should be informed by research and the exchange of examples of good practice. But are they? And if so how? Whilst we recognise that the implementation of learning technology takes place within a national and institutional context guided by policy, the main aim of this symposium is to focus on the relationships between research, theory and practice. The field of learning technology is beginning to mature into a recognised field of research. Questions begin to arise about the interplay and cross fertilisation of ideas between those that research the field of learning technology and those that support the implementation of learning technologies. This symposium brings together three people who will each present their view of learning technologists, their role, and the relationships with research and theory, from the perspective of research, theory and practice. Participants at the symposium will be asked to debate with speakers and each other, how we might use theories and research to address the issues learning technologists face in implementing and supporting learning technologies; how policies affect what we can do; and how experience could feed back into policy, research and theory.